Bergelimang Program: Community Innovation in Organic Waste Management in Banyumas Regency, Central Java - Yunianto Arif Suryawan; Agil Bagus Putra Perkasa; Muhson Arifin; Suci Trianingrum; Zukhruf Arifin (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
This study addresses the critical issue of waste management in Banyumas Regency, Central Java, where only 14.9% of waste was properly managed in 2024. This issue is further exacerbated by the significant reduction of Integrated Waste Disposal Sites (TPST) and the accumulation of approximately 26 tons of durian peel waste per harvest season in Alasmalang Village. To overcome this challenge, the Alasmalang community, supported by the CSR program of PT Pertamina Patra Niaga Fuel Terminal Maos, implemented “Bergelimang Program: Berdikari Mengelola Limbah Lingkungan”. This study employed a qualitative approach, utilizing in-depth interviews and desk research. The results highlight program innovations in transforming durian peel into environmentally friendly Class A fire extinguishers (APAR) by mixing durian peel powder with monoammonium phosphate (MAP), organic fertilizers for horticulture, and plant-based rodenticides utilizing flavonoids, polyphenols, and saponins. These innovations significantly contribute to environmental sustainability, advancing toward a net-zero waste movement, while simultaneously fostering economic empowerment in Alasmalang Village and its surrounding areas.